Implementation of Realistic Mathematic Education (RME) Model to Improve Learning Outcomes in Polyhedron - Hozaima; Agus Subaidi (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2023)
This research aims to improve the activity and learning outcomes of class VIII students at Islamic Junior High School Nasy-Atul Muta'allimin Candi. Researchers used the observation method to determine student activity, questionnaires to determine student responses to the Realistic Mathematics Education (RME) learning model, and tests to determine student learning outcomes improvement. The results of data analysis, it can be concluded that student activity from cycle I to cycle II experienced an increase of 0.23. Where in the first cycle an average of 3.01 was obtained and in the second cycle an average of 3.24 was obtained in the good category. Based on the student response questionnaire, it also increased from cycle I to cycle II by 25%, the percentage of students who answered